DEVELOPMENT OF INNOVATION MANAGEMENT TO INCREASE COMPETITIVENESS OF ENTERPRISES - Alieva Nadirakhon Abdumalikovna (PT ANTIS International Publisher, 2024)
The article highlights the features of managing the innovative activities of enterprises in order to increase competitiveness. The positive factors influencing the innovative activity of enterprises are analyzed, and the indicators that determine the effectiveness of innovation management are determined. The main tasks of managing innovation activities that serve the development of the enterprise are identified